Development and evaluation of a brief self-completed family history screening tool for common chronic disease prevention in primary care. - Walter, F; Prevost, A; Birt, L; Grehan, N; Restarick, K; Morris, H; Sutton, S; Rose, P; Downing, S; Emery, J (2013)
BACKGROUND: Family history is an important risk factor for many common chronic diseases, but it remains underutilised for diagnostic assessment and disease prevention in routine primary care. AIM: To develop and validate a brief self-completed family history questionnaire (FHQ) for systematic primary care assessment for family history of diabetes, ischaemic heart disease, breast cancer, and colorectal cancer. DESIGN AND SETTING: Two-stage diagnostic validation study in 10 general practices in eastern England. Method Participants aged 18-50 years were identified via random sampling from electronic searches of general practice records. Participants completed a FHQ then had a three-generational 'gold standard' pedigree taken, to determine disease risk category. In stage 1, the FHQ comprised 12 items; in stage 2 the shorter 6-item FHQ was validated against the same 'gold standard'. RESULTS: There were 1147 participants (stage 1: 618; stage 2: 529). Overall, 32% were at increased risk of one or more marker conditions (diabetes 18.9%, ischaemic heart disease 13.3%, breast cancer 6.2%, colorectal cancer 2.2%). The shorter 6-item FHQ performed very well for all four conditions: pooled data from both stages show diabetes, sensitivity = 98%, specificity = 94%; ischaemic heart disease, sensitivity = 93%, specificity = 81%; breast cancer, sensitivity = 81%, specificity = 83%; colorectal cancer, sensitivity = 96%, specificity = 88%, with an area under the receiver operating characteristic curve of 0.90 for males and 0.89 for females. CONCLUSION: This brief self-completed FHQ shows good diagnostic accuracy for identifying people at higher risk of four common chronic diseases. It could be used in routine primary care to identify patients who would be most likely to benefit from a more detailed pedigree and risk assessment, and consequent management strategies.